Do R&D intensity and capacity utilisation matter for SMEs' innovations within the CEE region? Testing moderating roles of different ownership structures. - Raymond Darfo-Oduro; Viktor Prokop; Jan Stejskal; Viktorie Klímová; Vladimír Žítek (PLoS ONE, 2024)
Existing innovation literature has assumed that the relationship between firms' R&D intensity and innovation take place without the interplay of other organizational factors. However, the reality differs, and research to date has shown that other factors affecting firms' innovation need to be considered. This is important especially in Central and Eastern Europe (CEE) countries, which are highly dependent on both internal and external R&D and are associated with an inability to use R&D resources effectively. This study therefore responds to calls for further analysis, especially within the CEE region, and focuses on the role of two factors affecting SMEs' innovativeness and their effects, which have been mixed so far. First, we investigate the effects of SMEs' R&D intensity and capacity utilisation on product innovation. Second, we reveal the moderating role of SMEs' different ownership structures (ownership concentration; private/public ownership; family/non-family ownership) in the relationship between R&D intensity and product innovation. We confirm that CEE SMEs' ownership concentration and private ownership moderate the relationship between R&D intensity and product innovation. In contrast, we reject our hypothesis expecting that family ownership of SMEs can significantly moderate the relationship between R&D intensity and product innovation. Interestingly, we also show that the relationship between capacity utilisation and innovation is non-linear (inverted U-shaped). This study makes a significant contribution in the form of analysis within the CEE region, whose innovation systems are seen to be weak, and it is therefore necessary to bring new knowledge and recommendations to managers and public policymakers.